2022
DOI: 10.3390/ijms24010193
|View full text |Cite
|
Sign up to set email alerts
|

Matched Analyses of Brain Metastases versus Primary Non-Small Cell Lung Cancer Reveal a Unique microRNA Signature

Abstract: Distant spreading of tumor cells to the central nervous system in non-small cell lung cancer (NSCLC) occurs frequently and poses major clinical issues due to limited treatment options. RNAs displaying differential expression in brain metastasis versus primary NSCLC may explain distant tumor growth and may potentially be used as therapeutic targets. In this study, we conducted systematic microRNA expression profiling from tissue biopsies of primary NSCLC and brain metastases from 25 patients. RNA analysis was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…MiR-335-5p and miR-34b-3p were identified as unique to NSCLC brain metastasis, with others such as miR-330-3p having a diagnostic potential [125,126]. Comparative studies identified specific miRNAs upregulated and downregulated in brain metastases compared to primary NSCLC tumors, highlighting the role of miRNAs in controlling tumor cell proliferation, migration, and invasion [127]. Notable findings include miR-596-3p's role in inhibiting brain metastases by modulating YAP1 and IL-8 and the significant downregulation of microRNA-375 in patients with brain metastases [128,129].…”
Section: Exosomes and Non-code Rnamentioning
confidence: 98%
“…MiR-335-5p and miR-34b-3p were identified as unique to NSCLC brain metastasis, with others such as miR-330-3p having a diagnostic potential [125,126]. Comparative studies identified specific miRNAs upregulated and downregulated in brain metastases compared to primary NSCLC tumors, highlighting the role of miRNAs in controlling tumor cell proliferation, migration, and invasion [127]. Notable findings include miR-596-3p's role in inhibiting brain metastases by modulating YAP1 and IL-8 and the significant downregulation of microRNA-375 in patients with brain metastases [128,129].…”
Section: Exosomes and Non-code Rnamentioning
confidence: 98%
“…Regarding NSCLC brain metastases, Tsakonas et al studied microRNA expression in patients with NSCLC primary tumors with metastatic brain NSCLC [ 18 , 19 ]. They found that compared to primary NSCLC tumor samples, there are five microRNAs upregulated (microRNA-219a-5p, microRNA-9-5p, microRNA-124-3P, microRNA-219a-2-3p, and microRNA-129-2-3p) in brain metastases, while six microRNAs are found to be downregulated (microRNA-199a-5p, microRNA-199b-5p, microRNA-142-3p, microRNA-199b-5p, microRNA-199a-3p, and microRNA-150-5p) [ 18 , 19 ].…”
Section: Reviewmentioning
confidence: 99%
“…Regarding NSCLC brain metastases, Tsakonas et al studied microRNA expression in patients with NSCLC primary tumors with metastatic brain NSCLC [ 18 , 19 ]. They found that compared to primary NSCLC tumor samples, there are five microRNAs upregulated (microRNA-219a-5p, microRNA-9-5p, microRNA-124-3P, microRNA-219a-2-3p, and microRNA-129-2-3p) in brain metastases, while six microRNAs are found to be downregulated (microRNA-199a-5p, microRNA-199b-5p, microRNA-142-3p, microRNA-199b-5p, microRNA-199a-3p, and microRNA-150-5p) [ 18 , 19 ]. In adenocarcinoma metastases, Zhao et al found that five microRNAs are upregulated ( microRNAs-9*, microRNA-1471, microRNA-718, microRNA-3656, microRNA-720) compared to primary lung adenocarcinoma, while three microRNAs were found to be downregulated (microRNAs-214, microRNA-145, microRNA-23a) [ 20 ].…”
Section: Reviewmentioning
confidence: 99%